Concordance of knowledge and abilities in the educational process: the analysis of achievements of the 6th form students - Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2005)
The achievements of 15 per sent of students fall short of the requirements to students’ abilities defined in General Curriculum Framework and Educational Standards. These students lack elementary understanding. For this reason the work with them has to be individualized; more attention has to be paid to the explanation of each step; well known context of the tasks that is close to their surroundings has to be used.About 30 per sent of students have mastered the completed course well and very well. These students are very different from the others. They do most standard operations without mistakes; similar results can be observed in the process of solving tasks of open or close type, or of different context. The work with the students who try to attain the basic level has to be differentiated because the skills of these students are not firm, their knowledge is fragmentary and sometimes not understandable, and their abilities to analyze conditions of a problem, to predict and assess the result, to choose the way of solution and to present it in most cases are insufficiently developed.
Keywords: the 6th form; the sphere of numeration; knowledge and skills; communicative skills; thinking skills; problem solving skills